Complex evaluation of agrotechnical factors in rape seed - Kátai, Zoltán (Acta Agraria Debreceniensis, 2010)
A polifactorial field trial with rape was carried out in the crop-years of 2007/2008 and 2008/2009 at the Látókép Research Centre of University of Debrecen, 15 km away from Debrecen. The soil type of the research area was a calcaric chernozem, with a levelled and homogeneous surface. Our investigations on the dynamics of lodging proved that rape can easily be lodged under unfavourable weather conditions, which results in a significant crop failure: In crop-year 2009 yields were 1.0-1.5 t ha-1 higher than in 2008, when the weather conditions were more unfavourable. In both crop-years the influence of sowing time on the crop yield of rape was examined in three soil cultivation systems, with ploughing, loosening or disking. Different sowing time influenced the yield of rape in both crop-years significantly. In the crop-year of 2007/2008 – due to mild winter – we got the highest yield in the first sowing time (at the end of August) with loosening (3930 kg ha-1) and disking (3727 kg ha-1), while in case of ploughing we experienced the highest yield (3770 kg ha-1) in the second sowing time. There were no significant differences between the first and second sowing time (the end of August and the beginning of September), and in the third sowing time (end of September) also a moderate crop failure (-6.7%) cold be obtained, due to the favourable weather in winter and the water supply of the crop-year 2007/2008. In 2008/2009 all the three cultivation systems showed the best yield-results in the second sowing time (ploughing: 4886 kg ha-1, loosening: 5186 kg ha-1, disking: 5090 kg ha-1), and the first sowing time hardly differed from this (-4.1%), while the late September sowing time resulted in a significant crop failure of -11.1%.